The Increasing Capacity of Rice Farmers through the Role Agricultural Extension - Bakari, Nurlailah; Managanta, Andri Amaliel; Tambingsila, Meitry (Indonesian Journal of Agricultural Research, 2022)
Agricultural extension agents are agents of change who are directly related to farmers The purpose of the extension is to change the behavior of farmers in terms of knowledge, attitudes, and skills so that farmers have a more prosperous life. Rice farmers in West Tojo District carry out farming activities that still rely on hereditary habits, causing farmers to lack the capacity to run food crop businesses, both technically in cultivation, harvesting, and marketing. The objectives of the study are (1) to determine the level of capacity of rice farmers in Kabalo Village Tojo Una-Una District and, (2) to determine the effect of the role of extension agents on increasing the capacity of rice farmers in Kabalo Village Tojo Una-Una District. This research was conducted from March 2020 to August 2020 in Kabalo Village West Tojo District Tojo Una-Una Regency. This study used a population sample of 56 rice farmers. Based on the results of this study, the role of agricultural extension agents had an effect on the success rate of rice farmers in Kabalo Village. Through increasing the role of extension workers, both facilitators, motivators, mediators, advisors, and communicators, could increase the capacity of farmers in managing capital, utilizing technology, labor, and marketing processes that benefit farmers.